Peran Subjective Well-Being dan Trust in The Employer terhadap Organizational Citizenship Behavior (OCB) Karyawan - Fatwa Tentama; Cita Yuliantin (Journal An-Nafs: Kajian Penelitian Psikologi, 2021)
Organizational citizenship behaviour is one of the behaviours that can affect the company's success, so it is necessary to study the factors that can influence it. This study examines the effect of subjective well-being and trust in the employer on employee organizational citizenship behaviour. The population in this study were 110 permanent employees at an automotive company in Yogyakarta. The research sample was 70 employees with the characteristics of working in an automotive company, a minimum of one year of service, a permanent employee who did not work in the workshop. The sample selection was male and female with a nonprobability purposive sampling technique. The research instrument used was organizational citizenship behaviour, subjective well-being, and trust in the employer scales. Hypothesis testing using multiple linear regression analysis with SPSS V.21 program. Simultaneous analysis results show a significant effect of subjective well-being and trust on employee organizational citizenship behaviour. The partial analysis shows a very significant positive effect of subjective well-being on organizational citizenship behaviour and trust in the employer on organizational citizenship behaviour. Subjective well-being and trust in the employer contributed 49% to organizational citizenship behaviour. The amount of contribution given by subjective well-being contribution is 20.66%, and trust in the employer is 28.31%. Thus trust in the employer provides a more dominant contribution to organizational citizenship behaviour